The Role of Bioenergy in a Climate-Changing World - Souza, Gaucia Mendes; Ballester, Maria Victoria R.; de Brito Cruz, Carlos Henrique; Chum, Helena; Dale, Bruce; Dale, Virginia H.; Fernandes, Erick C.M.; Foust, Tom; Karp, Angela; Lynd, Lee; Filho, Rubens Maciel; Milanez, Artur; et al. (Elsevier, 2018)
Bioenergy has been under intense scrutiny over the last ten years with significant research efforts in many countries taking place to define and measure sustainable practices. We describe here the main challenges and policy issues and provide policy recommendations for scaling up sustainable bioenergy approaches globally. The 2016 Intended Nationally Determined Contributions (INDCs defined under the UN Framework Convention on Climate Change) (UNFCCC) Conference of the Parties (COP21) will not reach global Greenhouse Gas (GHG) emission targets of 2 °C. Sustainable biomass production can make a significant contribution. Substantive evidence exists that many bioenergy cropping systems can bring multiple benefits and off-set environmental problems associated with fossil fuels usage as well as intensive food production and urbanization. We provide evidence that there are many approaches to land use for bioenergy expansion that do not lead to competition for food or other needs. We should focus on how to manage these approaches on a synergistic basis and how to reduce tradeoffs at landscape scales.